2019
DOI: 10.7554/elife.42448
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus co-opts host mitochondrial function to favour infectious virus production

Abstract: Although respiratory syncytial virus (RSV) is responsible for more human deaths each year than influenza, its pathogenic mechanisms are poorly understood. Here high-resolution quantitative imaging, bioenergetics measurements and mitochondrial membrane potential- and redox-sensitive dyes are used to define RSV’s impact on host mitochondria for the first time, delineating RSV-induced microtubule/dynein-dependent mitochondrial perinuclear clustering, and translocation towards the microtubule-organizing centre. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
96
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(110 citation statements)
references
References 58 publications
13
96
1
Order By: Relevance
“…To investigate if SARS-CoV-2 spike protein induces production of pro-inflammatory cytokines, we used a minimally immortalised human bronchial epithelial cell line BCi-NS1.1, which was derived from human primary bronchial epithelial cells (Hayman et al, 2019;Hu et al, 2019;Kedzierski et al, 2017;Walters et al, 2013). BCi-NS1.1 was stimulated with histidine (His)-tagged CoV2-S1, CoV2-RBD, or CoV-S1 or CoV-RBD.…”
Section: Sars-cov-2 Spike Protein S1 and Rbd Induces Elevated Inductimentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate if SARS-CoV-2 spike protein induces production of pro-inflammatory cytokines, we used a minimally immortalised human bronchial epithelial cell line BCi-NS1.1, which was derived from human primary bronchial epithelial cells (Hayman et al, 2019;Hu et al, 2019;Kedzierski et al, 2017;Walters et al, 2013). BCi-NS1.1 was stimulated with histidine (His)-tagged CoV2-S1, CoV2-RBD, or CoV-S1 or CoV-RBD.…”
Section: Sars-cov-2 Spike Protein S1 and Rbd Induces Elevated Inductimentioning
confidence: 99%
“…BCi-NS1.1 cells were obtained from Prof. Ronald Crystal Laboratory at Weill Cornell Medical College, and Memorial Sloan-Kettering Cancer Center, New York, NY, USA) (Walters et al, 2013). The cells were cultured in hormone supplemented Bronchial Epithelial Cell Growth Media (BEGM; Lonza, Switzerland) supplemented with 50U/mL penicillin and streptomycin (Hayman et al, 2019;Hu et al, 2019;Kedzierski et al, 2017).…”
Section: Cell Linementioning
confidence: 99%
“…Several reports have shown that HRSV induces oxidative stress in infected cells, resulting in increased levels of oxidized glutathione [25][26][27][28]. Actually, increased production of mitochondrial reactive oxygen species (ROS) favors HRSV production, suggesting new potential therapeutic approaches against this virus [63]. The cells usually upregulate the synthesis of glutathione and polyamines (putrescine, spermidine, and spermine) to counteract that stress.…”
Section: Oxidative Stress: Glutathione System and Polyaminesmentioning
confidence: 99%
“…In addition, exaggerated production of mtROS results in fungus-mediated pathological inflammation in airway epithelial cells (40) and T. cruzi-mediated cardiomyopathy in Chagas disease (46). Also, mtROS inhibition suppressed respiratory syncytial virus replication and virus-mediated lung inflammation (47). These data suggest the pathogenic role of mtROS during infections of various pathogens.…”
Section: Detrimental Roles Of Mtros During Infection and Sepsis Mtrosmentioning
confidence: 87%
“…Numerous viruses co-opt host mitochondrial functions and mtROS to favor their pathogenesis and virulence ( Table 1). A recent study showed that respiratory syncytial virus infection resulted in the impairment of mitochondrial respiration, loss of mitochondrial membrane potential, and increased mtROS, which promoted and favored viral replication in the cells (47). In addition, human immunodeficiency virus (HIV) can suppress or enhance mtROS generation in both productive and non-productive stages for its own benefit.…”
Section: Viruses Manipulate Host Mtros For Pathogenesismentioning
confidence: 99%